Qat dan Krisis Kemanusiaan Yaman: Studi Perubahan Nilai dalam Takhzeen Al-Qat - Apipudin; Nurul Hasna Khoirunnisa (Nady Al-Adab : Jurnal Bahasa Arab, 2023)
Qat has been known by the people of Africa and South Arabia for centuries. In Yemen, qat is often referred to as ‘the plant from heaven'. The tradition of chewing qat, known as takhzeen al-qat, creates positive social interactions among Yemeni people. Currently, the cultural value of takhzeen has shifted from positive to negative. The consumption of qat has changed from being a form of entertainment to a harmful social custom. This study examines the changes in the value of the takhzeen al-qat tradition in Yemen. The theories applied in this study are the theory of cultural change theory and the humanitarian crisis. The qualitative study method is used along with data collection techniques through literature reviews. This study concludes that qat came from Ethiopia around the 13th century AD, popularized by the Sufis in Yemen. At the beginning of its appearance, takhzeen qat was considered positively by the Yemeni people. When the Yemen crisis hit, takhzeen qat turned into a social custom. The negative impact of takhzeen qat during the crisis is enhancing malnutrition cases and qat addiction. Changes in the value of takhzeen qat changed due to the impetus of the humanitarian crisis that occurred in Yemen. Changes in the cultural values ​​of takhzeen qat occur due to several factors, such as social conflicts, new discoveries, and the foreign cultures' intervention in the midst of the humanitarian crisis that occurred in Yemen become the main reasons for shifting values ​​in the takhzeen qat tradition Keywords: Khat, Yemeni Crisis, Cultural Shift, Qat, Yemen